PENERAPAN ASAS PRADUGA TAK BERSALAH TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM PADA PROSES PENYIDIKAN - Annisa Famela; Iza Rumesten (Fakultas Hukum Universitas Sriwijaya, 2024)
In examining a child in conflict with the law aged under 12 years does not determine the status of a suspect and at the end of this process the judge only gives a determination not a decision so that it raises doubts in the application of the presumption of innocence to the handling of children in conflict with the law who are not yet 12 years old. The problem of this research is how to apply the principle of the presumption of innocence to children who are in conflict with the law aged under 12 years and how the legal protection for children who are in conflict with the law aged under 12 years in the future. This study uses normative legal research. The results of the study show that the application of the principle of the presumption of innocence to children in conflict with the law aged under 12 years can be seen from the fulfillment of children's rights in undergoing the criminal justice process. The judge's determination needs to add consideration to community research reports, professional social worker research reports, as well as evidence to create protection, justice and legal certainty for the parties.